2011
DOI: 10.1093/cid/ciq049
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Placental Infection Modulate the Appearance of Drug-Resistant Plasmodium falciparum in Pregnant Women who Receive Intermittent Preventive Treatment

Abstract: IPTp with SP increases the prevalence of resistance markers in the placenta and in HIV-infected women at delivery, which suggests that host immunity is key for the clearance of drug-resistant infections. However, this effect of IPTp is limited to the period when blood levels of SP are likely to be significant and does not translate into more-severe infections or adverse clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 32 publications
4
24
2
Order By: Relevance
“…40 New evidence suggests that malaria parasites are more likely to develop wildtype mutations following exposure to sulfadoxine-pyrimethamine as intermittent preventive treatment during pregnancy (IPTp) when administered to HIVpositive women. 41 The interaction between STIs/RTIs and HIV has been well established, although providing presumptive treatment for STIs/RTIs to pregnant women in Rakai, Uganda, has not shown protective effect against maternal to child transmission of HIV. 42 However, malaria chemoprophylaxis was not provided in this study; therefore, the potential modulating effect of malaria on maternal to child transmission in the presence of STIs/RTIs remains unknown.…”
Section: Commentmentioning
confidence: 99%
“…40 New evidence suggests that malaria parasites are more likely to develop wildtype mutations following exposure to sulfadoxine-pyrimethamine as intermittent preventive treatment during pregnancy (IPTp) when administered to HIVpositive women. 41 The interaction between STIs/RTIs and HIV has been well established, although providing presumptive treatment for STIs/RTIs to pregnant women in Rakai, Uganda, has not shown protective effect against maternal to child transmission of HIV. 42 However, malaria chemoprophylaxis was not provided in this study; therefore, the potential modulating effect of malaria on maternal to child transmission in the presence of STIs/RTIs remains unknown.…”
Section: Commentmentioning
confidence: 99%
“…Indeed, although IPTp-SP has been associated with the selection of mutations [10, 1315], it has been shown that self-reported use of IPTp-SP did not increase the prevalence of resistant alleles [5, 16]. Moreover, conflicting results about the impact of mutant parasites on pregnancy outcomes such as parasite densities, maternal haemoglobin level, and anaemia have been reported [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an increased prevalence of resistant malaria parasites has been found in HIV-positive versus HIV-negative pregnant women [16]. The mechanisms promoting malaria drug resistance in HIV-coinfected hosts are expected to be similar to those promoting TB drug resistance in HIV–TB infections, but evidence is largely lacking.…”
Section: Immune Modulationmentioning
confidence: 99%